Lignin depolymerization into aromatic monomers over solid acid catalysts - Deepa, Ayillath K.; Dhepe, Paresh Laxmikant (ACS Catalysis, 2015)
It is imperative to develop an efficient and environmentally benign pathway to valorize profusely available lignin, a component of nonedible lignocellulosic materials, into value-added aromatic monomers, which can be used as fuel additives and platform chemicals. To convert lignin, earlier studies used mineral bases (NaOH, CsOH) or supported metal catalysts (Pt, Ru, Pd, Ni on C, SiO2, Al2O3, etc.) under a hydrogen atmosphere, but these methods face several drawbacks such as corrosion, difficulty in catalyst recovery, sintering of metals, loss of activity, etc. Here we show that under an inert atmosphere various solid acid catalysts can efficiently convert six different types of lignins into value-added aromatic monomers. In particular, the SiO2Al2O3 catalyst gave exceptionally high yields of ca. 60% for organic solvent soluble extracted products with 95 +/- 10% mass balance in the depolymerization of dealkaline lignin, bagasse lignin, and ORG and EORG lignins at 250 degrees C within 30 min. GC, GC-MS, HPLC, LC-MS, and GPC analysis of organic solvent soluble extracted products confirmed the formation of aromatic monomers with ca. 90% selectivity. In the products, confirmation of retention of aromatic nature as present in lignin and the appearance of several functional groups has been carried out by FT-IR and H-1 and C-13 NMR studies. Further, isolation of major products by column chromatography was carried out to obtain aromatic monomers in pure form and their characterization by NMR is presented. A detailed characterization of six different types of lignins obtained from various sources helped in substantiating the catalytic results obtained in these reactions. A meticulous study on fresh and spent catalysts revealed that the amorphous catalysts are preferred to obtain reproducible catalytic results.
Keywords: aromatic monomers; Biomass; column chromatography; depolymerization; lignin; solid acid catalysts